La paradoja del regreso - Llamosa Escovar, David Francisco (Bitácora Urbano Territorial, 2006)
This article explains the travel or the journey as a way to study the different problems that appear with the exodus: the journey means the return to the departure place, moment in which the traveller recognise all that he leaves, which means the past, the oblivion, the nostalgia, the absence and the memory. Among the others, these will be the subjects that the author will take in place from a literary and philosophical perspective, to go down to reflections on architectonic and urban matter, associate with time and space.